PRINSIP KESATUAN PANCASILA DALAM MEMBENTUK MASYARAKAT YANG HARMONIS - Pebryna Riosa Siburian (Publikasi Inspirasi Indonesia, 2024)
Pancasila, as the basis of the Indonesian state, functions as a symbol of national identity that combines various elements that form the nation's character. Of the five principles that form the foundation of Pancasila, the principle of unity has a crucial role in creating a harmonious society. This unity is reflected in relations between citizens as well as in the formation and development of a just, prosperous and prosperous society. In the history of the Indonesian nation, Pancasila has become a guide for national development. The principle of unity emphasizes the importance of cooperation and equality to achieve common goals. This research uses qualitative methods with a literature study approach to understand how the principle of Pancasila unity can be applied in forming a harmonious society, as well as the challenges faced in its implementation. Theoretical analysis shows that the unity promoted by Pancasila includes cooperation and equality in achieving mutual progress, with recognition and respect for differences as an important element. Implementation of the principle of Pancasila unity covers various aspects of community life, including political, social, cultural and economic. The main challenges in implementing this include integrating Pancasila values ​​in daily life, maintaining awareness of these values ​​amidst social dynamics and technological developments, as well as developing awareness among state officials.